Формування технологічних умінь у майбутніх інженерів-педагогів швейного профілю - Ковальська, В. С.; Безкоровайна, М. М.; Агапова, М. О. (НТУ "ХПІ", 2015)
У статті наведено результати розроблення методики формування технологічних умінь у майбутніх інженерів-педагогів швейного профілю. Визначено поняття “уміння”, “професійні уміння”, “технологічні уміння”. Розроблено модель формування технологічних умінь у майбутніх інженерів-педагогів швейного профілю, яка містить такі компоненти: цілемотиваційний, змістовний, організаційно-діяльнісний, оціночно-результативний. Модель стала основою побудови методики формування технологічних умінь у майбутніх інженерів-педагогів швейного профілю в процесі вивчення дисципліни “Технологія швейних виробів”, до компонентів якої належать мета, завдання, принципи, зміст, способи реалізації та критерії оцінювання. Основою реалізації методики обрано інноваційні технології навчання: “Акваріум” ‒ майстерні; “Алгоритм-лабіринт” ‒ метод завдань; брифінг-групи ‒ метод інцидентів; “Папка з вхідними документами” ‒ метод кейсів; групова динаміка ‒ мозковий штурм; дебати ‒ програмовані інструкції; дискусія ‒ розмова; кейс-технології, тренінги, ігри ‒ рішення вузькоспеціальних питань; короткочасні ротації ‒ рольові ігри.

The results of development of methods of formation of technological abilities at the future engineers-teachers sewing profile are presents in this article. The concepts of "skill", "professional skills", "technological skills." The model of formation of technological abilities at the future engineers-teachers sewing profile, which contains the following components: motivational, informative, organizational-activity, assessment and performance. The developed model was the basis for the construction of a methods of formation of technological abilities at the future engineers-teachers in the process of sewing profile of the discipline "Technology of garments", the components of which include the goals, objectives, principles (scientific, systematic and consistency, accessibility, communication training with practice activities, clarity, emotional learning, innovation), the content, methods of implementation and evaluation criteria. Content methods presented theoretical and practical parts in a 2 modules: Module 1 "The technology of processing individual parts outerwear", module 2 "Processing Technology clothing costume Coat-range." The basis for implementation of innovative technologies chosen method of learning, such as: "Aquarium" - workshops; "Algorithm-labyrinth" - a method of tasks; Briefing the group - a method of incidents; "A folder with incoming documents" - a method of case studies; group dynamics brainstorming; Debates - programmed instructions; discussion; Case technology, training, games - a decision highly specialized issues; short rotation - role-playing games. The criteria for evaluation of methods to determine the motivation of educational activity, the level of development of technological skills, the students' ability to self-control and self-esteem.
Formation of technological abilities at the future engineers-teachers sewing profile
Keywords: модель; методика; технології інноваційні; technological abilities; model; methods; innovative technologies